(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The management of waste plastics presents a significant difficulty in both India and globally due to the escalating consumption of plastics and their extensive decomposition time, spanning many centuries. Therefore, it is imperative to employ efficient strategies for the utilisation of these plastic materials. The primary aim of this study was to examine the viability of utilising waste polyethylene waste (PEW) as a partial substitute for aggregates in the manufacturing of concrete pavement mixtures. This study utilised cement, sand, coarse aggregate, and polyethylene waste (PEW). PEW was utilised as a substitute for aggregates by volume at several percentages, namely 0%, 10%, 20%, and 30%. The findings of the study indicate that the substitution of 5% of the coarse aggregate with PEW waste resulted in an 11% increase in the 28-day splitting tensile strength of the concrete pavement mix. Furthermore, the compressive and flexural strengths of the concrete mix in question exceeded the minimum compressive and flexural values specified by the concrete mix guide. Based on the findings of the test results, it is advised that the utilisation of PEW exceeding 5% of the coarse aggregate composition in the mixture be employed for the construction of low traffic pavements, rural roads and pavements. The redesigned pavement blocks are deemed to have the potential to make a significant contribution towards the global management of plastic waste.